Lessons learned in adapting an online intervention program for posttraumatic stress for use in Egypt. (February 2021) - Ellis, Kate; Miller-Graff, Laura E.
Cultural adaptation of evidence-based treatments is a pressing priority for global health, and previous research has informed recommendations for guiding the process of translation and adaptation. As research in the domain of cultural adaptation and evaluation of evidence-based treatments progresses, it is critical that researchers communicate key lessons learned, so that models of adaptation can be continuously refined and reconsidered. The work described in this article aimed to translate and culturally adapt an online intervention to address symptoms of posttraumatic stress—the PTSD Coach Online—for use with young adults in Egypt. The cultural adaptation framework proposed by Bernal and colleagues (1995) was used, and focus groups and interviews with members of the target population, mental health professionals, and service users were conducted. The authors encountered a number of challenges in treatment adaptation that generated important insights for future work. Specifically, this case study highlights the importance of translation teams with diverse backgrounds and experiences, the critical nature of iterative feedback throughout the adaptation process, and the importance of a long time-horizon for optimal adaptation.